(untitled) (Simbiótica. Revista Eletrônica, 2020)
This article analyzes from a theoretical and sociological perspective the situation of the pandemic caused by Coronavirus (SARS-CoV-2) and COVID-19 disease. Using conceptual tools of social systems theory, three “notes” are proposed for the study of the phenomenon, which consist of codes or conceptual pairs: normal/pathological, order/disorder, morphostasis/morphogenesis. Keywords: COVID-19; SARS-CoV-2; social systems theory; conceptual pairs.